In vivo functional analysis of Drosophila Robo1 immunoglobulin-like domains. Issue 1 (December 2016) - Reichert, Marie; Brown, Haley; Evans, Timothy
Abstract Background In animals with bilateral symmetry, midline crossing of axons in the developing central nervous system is regulated by Slit ligands and their neuronal Roundabout (Robo) receptors. Multiple structural domains are present in an evolutionarily conserved arrangement in Robo family proteins, but our understanding of the functional importance of individual domains for midline repulsive signaling is limited. Methods We have examined the functional importance of each of the five conserved immunoglobulin-like (Ig) domains within theDrosophila Robo1 receptor. We generated a series of Robo1 variants, each lacking one of the five Ig domains (Ig1-5), and tested each for their ability to bind Slit when expressed in culturedDrosophila cells. We used a transgenic approach to express each variant inrobo1's normal expression pattern in wild-type androbo1 mutant embryos, and examined the effects of deleting each domain on receptor expression, axonal localization, regulation, and midline repulsive signaling in vivo. Results We show that individual deletion of Ig domains 2–5 does not interfere with Robo1's ability to bind Slit, while deletion of Ig1 strongly disrupts Slit binding. None of the five Ig domains (Ig1-5) are individually required for proper expression of Robo1 in embryonic neurons, for exclusion from commissural axon segments in wild-type embryos, or for downregulation by Commissureless (Comm), a negative regulator of Slit-Robo repulsion inDrosophila. Each of the Robo1 Ig deletion variants (with the exception of Robo1∆Ig1) were able to restore midline crossing inrobo1 mutant embryos to nearly the same extent as full-length Robo1, indicating that Ig domains 2–5 are individually dispensable for midline repulsive signaling in vivo. Conclusions Our findings indicate that four of the five Ig domains withinDrosophila Robo1 are dispensable for its role in midline repulsion, despite their strong evolutionary conservation, and highlight a unique requirement for the Slit-binding Ig1 domain in the regulation of midline crossing.